Measuring progress - Kelsey J. O'Connor (Institute of Labor Economics (IZA), 2022)
Societal progress is characterized primarily as an improvement in the distribution of wellbeing; however, a small set of additional variables are also necessary. Social indicators based on objective measures are inherently limited by the subjective assessments necessary of "experts" to select and combine measures into indicators. Subjective well-being overcomes this limitation but is insufficient to guide all policy decisions and address certain issues, especially those relating to future concerns. Subjective well-being is the single most important, but necessarily not the only, indicator of progress. This entry also briefly discusses: recent history of well-being measurement; what makes people better off in theory; the difference between subjective and 'objective' measures of well-being; their limitations; what we need to improve measures of progress, and examples of government implementation of well-being indicators.
Keywords: I31; O10; 330; well-being; wellbeing; societal progress; quality of life; GDP; subjective well-being; social indicators; beyond GDP; SDGs; life satisfaction